Pattern of Thyroid Disorders in a Tertiary Care Centre of a High-Altitude Region of Nepal: A hospital-based retrospective study - Shah, Tirtha Narayan; Anu, Anuraj; Bista, Binamra (Journal of Karnali Academy of Health Sciences, 2024)
Background: Millions of people globally suffer from thyroid disorders, with over half of them are unaware of their conditions. Untreated, these disorders can lead to severe health complications such as heart problems, pregnancy complications, goiter, bone health issues, etc. Jumla, a high altitude Himalayan region in Nepal, includes iodine-deficient areas, making it prone to thyroid disorders. This study aimed to identify the prevalence and pattern of thyroid disorders in this region.Methods: A retrospective hospital-based cross-sectional study was conducted using data from the Karnali Academy of Health Sciences, Jumla, spanning from 1st January–31st December 2023. Participants of all ages with complete thyroid function test results (fT3, fT4, and TSH assessed via chemiluminescence immunoassay) were included. Data were extracted from Bahmni EMR, cleaned in MS-Excel, and analyzed in R software, with a significance threshold of p < 0.05. Results: Among 816 participants (mean age: 35.66 ± 14.60 years), 660 (80.8%) were female, and 156 (19.1%) were male. The most represented age group was 25–34 years. Subclinical hypothyroidism was the most prevalent disorder, affecting 33 males (21.15%) and 143 females (21.66%). Primary hyperthyroidism was the least common, found in 1 male (0.64%) and 7 females (1.06%). Other disorders included secondary hypothyroidism, secondary hyperthyroidism, primary hypothyroidism, and subclinical hyperthyroidism.Conclusion: Subclinical hypothyroidism was the most common thyroid disorder, with females disproportionately affected. Wider population screening for early detection and management is essential to mitigate health risks.